Computer-aided translation tools – the uptake and use by Danish translation service providers - Tina Paulsen Christensen; Anne Schjoldager (JoSTrans: The Journal of Specialised Translation)
The paper reports on a questionnaire survey from 2013 of the uptake and use of computer-aided translation (CAT) tools by Danish translation service providers (TSPs) and discusses how these tools appear to have impacted on the Danish translation industry. According to our results, the uptake in Denmark is rather high in general, but limited in the case of machine translation (MT) tools: While most TSPs use translation-memory (TM) software, often in combination with a terminology management system (TMS), only very few have implemented MT, which is criticised for its low quality output, especially when Danish is one of the languages, though some also express willingness to consider using MT (more) when output quality improves. Most respondents report that CAT has changed the translation industry, mentioning that the technology facilitates improved productivity and consistency, but also that sometimes it results in lower prices and decreasing output quality.